2019
DOI: 10.3390/cancers11111668
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor and miRNA Interplays Can Manifest the Survival of ccRCC Patients

Abstract: Clear cell renal cell carcinoma (ccRCC) still remains a higher mortality rate in worldwide. Obtaining promising biomakers is very crucial for improving the diagnosis and prognosis of ccRCC patients. Herein, we firstly identified eight potentially prognostic miRNAs (hsa-miR-144-5p, hsa-miR-223-3p, hsa-miR-365b-3p, hsa-miR-3613-5p, hsa-miR-9-5p, hsa-miR-183-5p, hsa-miR-335-3p, hsa-miR-1269a). Secondly, we found that a signature containing these eight miRNAs showed obviously superior to a single miRNA in the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 76 publications
1
48
0
2
Order By: Relevance
“…However, the diagnosis of ccRCC is yet confronted with problems such as lacking biomarkers. Therefore, more effective therapy for improving the diagnosis and prognosis of patients with ccRCC is a prerequisite to developing promising molecular biomarkers ( Qin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis of ccRCC is yet confronted with problems such as lacking biomarkers. Therefore, more effective therapy for improving the diagnosis and prognosis of patients with ccRCC is a prerequisite to developing promising molecular biomarkers ( Qin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the 2 miRNAs (hsa-miR-9-5p and hsa-miR-183-5p) and 3 lncRNAs (CTD-2228K2.7, HOTAIRM1 and NCF1C), the expression of hsa-miR-9-5p could be downregulated by lncRNA TUG1, and TUG1 overturned the effect of miR-9-5p on the proliferation, colony formation, cell cycle arrest, and apoptosis in bone SARCs cells [40]. Hsa-miR-183-5p was the rst found in SARCs, highly expressed hsa-miR-183-5p might be associated with a poor prognosis for Clear cell renal cell carcinoma patients [41]. In addition, it was also considered as the optimal diagnostic biomarkers for hepatocellular carcinoma [42].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies involving cRCC have reported the importance of the six miRNAs (hsa-mir-222, hsa-mir-204, hsa-mir-206, hsa-mir-183, hsa-mir-372, hsa-mir-221) in the ceRNA network. In particular, hsa-mir-206, hsa-mir-204, and hsa-mir-372 were found to suppress cancer through corresponding biological functions [50][51][52], and hsa-mir-183 was considered to be a potential oncogene [53]. Kaplan-Meier analysis also showed that high expression of LINC00520 had an effect on OS.…”
Section: Discussionmentioning
confidence: 96%